Pool boiling enhancement via nanotexturing and self-propelled swing motion for bubble shedding. (April 2022) - Kim, Yong Il; Bang, Boo-Hyoung; Jang, Keunhee; An, Seongpil; Yarin, Alexander L.; Yoon, Sam S.
Abstract: Vapor bubbles were shed from the heater surface by self-propelled swinging resulting from rising bubbles for improved heat dissipation. The heating wire was electroplated, and thus nanocones were formed on its surface. This nanotextured wire was attached to polyamide tape and underwent Joule heating. The vapor bubbles on the wire induced the self-propelled motion of the heater plates assembled in a "Λ" shape suspended at the tip. The growing bubbles experienced competing forces in the form of buoyancy and surface tension. Eventually, buoyancy dominated and, as a result, the heater plate was propelled in the direction of the rising bubbles. The nanotextured surface increased the number of bubble nucleation sites, and thus, the displacement of the swing motion was magnified accordingly, owing to enhanced bubble detachment. The sustainable swing motion was motorized to enable the temperature of the wire heater to be accurately measured. In these motorized experiments, the critical heat flux (CHF) and effective convective heat transfer coefficient ( h eff ) increased when the amount of nanotexturing on the heating wire increased, which confirmed the benefits of nanotexturing on pool boiling in which self-propelled swing motion was utilized to shed the nucleated bubbles.